2012
DOI: 10.1017/s1355617712000902
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Postconcussion Symptoms and Functional Outcomes in OEF/OIF Veterans with Self-Report of Blast Exposure

Abstract: Postconcussion symptoms (PCS) and functional outcomes were evaluated in 91 OEF/OIF outpatient veterans with reported histories of blast-exposure, with the goal of evaluating (1) the association between these outcomes and a clinical diagnosis of mild traumatic brain injury (mTBI) with or without loss of consciousness (LOC); and (2) the influence of post-traumatic stress disorder (PTSD) and depression on PCS reporting and perceived functional limitations. Individuals who reported mTBI with LOC had greater PCS co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 58 publications
4
54
1
Order By: Relevance
“…The exacerbation of depression and PTSD symptoms after concussive brain injury is consistent with investigations examining patients with blast TBI after loss of consciousness, 17 self-report surveys in Operation Enduring Freedom and Operation Iraqi Freedom veterans, 23 and subjective complaint measures comparing predeployment and postdeployment. 43 A recent retrospective study 44 reported similar findings specifically in Marines at 3 months after deployment; however, questions remained about the generalizability to other branches of the military and the longer-term effect on outcomes.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The exacerbation of depression and PTSD symptoms after concussive brain injury is consistent with investigations examining patients with blast TBI after loss of consciousness, 17 self-report surveys in Operation Enduring Freedom and Operation Iraqi Freedom veterans, 23 and subjective complaint measures comparing predeployment and postdeployment. 43 A recent retrospective study 44 reported similar findings specifically in Marines at 3 months after deployment; however, questions remained about the generalizability to other branches of the military and the longer-term effect on outcomes.…”
Section: Discussionsupporting
confidence: 77%
“…17,18 Findings from previous investigations comparing patients with blast vs nonblast TBI vary. Specifically, similarities have been observed in neurocognitive performance, 14,19,20 symptom complaints, 6,20 and mental health, 5,20 while other investigations have found individuals with blast TBI to be worse compared with individuals with nonblast TBI in all 3 of these domains 13 or solely in mental health.…”
mentioning
confidence: 99%
“…Individuals were stratified based on whether they suffered a mTBI (n=50) or not (n=25) due to a blast exposure (see Methods). Participants were part of a larger research study involving neuropsychological testing, diagnostic interviews, and self-report questionnaires (see Verfaellie, Lafleche, Spiro, Tun, & Bousquet, 2013). Exclusion criteria for the larger study (see Verfaellie et al, 2013) included history of psychosis or neurological diagnosis except mTBI.…”
Section: Participantsmentioning
confidence: 99%
“…Participants were part of a larger research study involving neuropsychological testing, diagnostic interviews, and self-report questionnaires (see Verfaellie, Lafleche, Spiro, Tun, & Bousquet, 2013). Exclusion criteria for the larger study (see Verfaellie et al, 2013) included history of psychosis or neurological diagnosis except mTBI. Participants were also excluded if they demonstrated questionable effort (i.e., below 45 on the retention trial of the Test of Memory Malingering; Tombaugh, 1996).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation